ALPROSTADIL ASSOCIATED FEVER IN THE NEWBORN: SIDE EFFECT OR INFECTION?. Issue 1 (14th December 2015) - Swaid, Sohair Bshara; Vardi, Amir; Perlman, Amichai; Matok, Ilan
Abstract : Background: Alprostadil is a prostaglandin used to maintain patent ductus arteriosus in neonates with ductus arteriosus dependent congenital heart malformations. Alprostadil administration results in fever in ∼14% of treated neonates. The occurrence of fever in this setting, often leads to extensive investigations to identify the source of fever, as well as to empiric antibiotic therapy and the postponement of cardiac surgery. These measures can lead to several neonatal complications. Aim: To identify clinical and laboratory criteria that can help determine the likelihood that fever during alprostadil therapy is due to infection. Methods: Using a case control study design, we evaluated neonates who were admitted to the pediatric cardiac intensive care department between 2009 and 2014, and who developed fever during alprostadil treatment. Neonates with infection and without were compared to identify early clinical symptoms and biomarkers that can serve as predictors of infection. Analyses included univariate and multivariate methods. Results: Our study included 124 neonates. Seventy neonates experienced infection (median age 9 days (IQR 4–15.2)) and fifty-four did not (median age 5 days (IQR 2–11)). Factors preceding fever and predicting infection included: White blood cell count (WBC) above 10000/microL (HR=1.97, 95% CI 1.02–3.74), or platelet count above 440 K/microL (HR=2.27, 95%CI=1.32–5.23). Increases in WBC or lactate, before fever onset, were also associated with infection. Conclusions: Elevations in WBC, platelets and lactate before fever onset were associated with infection. These results may assist in decisions regarding cardiac surgery timing in neonates treated with alprostadil.